2009
DOI: 10.4049/jimmunol.0801892
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Preconditioning Protects Neurons via Neuron-Specific Up-Regulation of CREB-Binding Protein

Abstract: Despite being a proinflammatory cytokine, tumor necrosis factor-α (TNF-α) preconditions neurons against various toxic insults. However, underlying molecular mechanisms are poorly understood. The present study identifies the importance of CREB-binding protein (CBP) in facilitating TNF-α-mediated preconditioning in neurons. Treatment of rat primary neurons with fibrillar amyloid-β 1–42 (Aβ) resulted in the loss of CBP protein. However, this loss was compensated by TNF-α preconditioning as the expression of neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 60 publications
0
47
0
Order By: Relevance
“…Hippocampal neurons were isolated from fetuses (E18) of pregnant female mice as described by us (Jana et al, 2007; Saha et al, 2009). Briefly, dissection and isolation procedures were performed in an ice-cold, sucrose buffer solution (sucrose 0.32 M, Tris 0.025 M; pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Hippocampal neurons were isolated from fetuses (E18) of pregnant female mice as described by us (Jana et al, 2007; Saha et al, 2009). Briefly, dissection and isolation procedures were performed in an ice-cold, sucrose buffer solution (sucrose 0.32 M, Tris 0.025 M; pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…6D). Evidence suggests that TNF-a is an upstream inducer of DNA binding activity of CREB and C/EBP-b (Saha et al, 2009;Wang et al, 2010). The DNA-protein complex formed with CREB and C/EBP-b in JEV-infected microglia decreased in the presence of TNF-a neutralizing antibody.…”
Section: C/ebp-b and Creb Contributed To Jev-induced Glutaminase Exprmentioning
confidence: 99%
“…Indeed, drugs targeted to increase specific CBP expression could reach the threshold of CBP molecules necessary to activate correct genetic programs with more precisions than solely modulating histone acetylation levels. Pharmacological modulation of CBP levels has been reported recently (Saha et al, 2009): preconditioning of neurons with TNF-a protected them from degenerative conditions (and particularly Ab toxicity) through a neuron-specific increase of CBP expression. The authors suggested that an 'adequate' amount of CBP is required at a basal level to ensure pro-survival functions.…”
Section: Cbp Expression and Sensitivity In Neuronal Functionsmentioning
confidence: 99%